Perceptions of Vocational High School Teachers on Organizational Commitment: Malatya Example - Gürbüz, Oğuz; Demirkol, Murat; Özdemir, Tuncay Yavuz (Şahin ORUÇ, 2023)
This research tries to determine the perceptions of vocational high school teachers about organizational commitment. In this context, it is aimed to determine the internal and external factors affecting the organizational commitment of vocational high school teachers and to determine the effects of administrators on teachers' organizational commitment. The universe of the research consists of teachers working in vocational high schools in Battalgazi and Yeşilyurt districts of Malatya. 21 teachers working in the same districts participated in the research. The Phenomenology design of qualitative research was used as the research method. The data were collected with a semi-structured interview form with 4 questions aiming to reveal the internal and external factors affecting the organizational commitment of vocational high school teachers and analyzed with descriptive analysis technique. In the results of working; It has been determined that the school management's attitude, the harmony of the teacher staff and the school branch harmony come to the fore among the in-school factors affecting the commitment. While the culture lesson teachers talk about the disadvantages they experience in vocational high school due to their branches; on the other hand, vocational course teachers emphasized the advantages of their branches. While it was determined that the most positive factors affecting the teachers' commitment levels out of school, social activities, related parents and the positive image of the school outside, it was determined that individual problems arising from their private lives, financial dissatisfaction and loss of professional reputation also negatively affected their commitment. of teachers; It has been determined that the situation they expect the most from school administrators and senior management is to be valued. In addition, it was concluded that teachers and administrators should always have a positive view of events.
Keywords: Applied and Developmental Psychology (Other); Uygulamalı ve Gelişimsel Psikoloji (Diğer)